2009
DOI: 10.1111/j.1530-0277.2009.00927.x
|View full text |Cite
|
Sign up to set email alerts
|

Expression Pattern, Ethanol‐Metabolizing Activities, and Cellular Localization of Alcohol and Aldehyde Dehydrogenases in Human Pancreas: Implications for Pathogenesis of Alcohol‐Induced Pancreatic Injury

Abstract: Alcohol dehydrogenase and ALDH family members are differentially expressed in the various cell types of pancreas. ADH1C may play an important role in modulation of activation of pancreatic stellate cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 47 publications
2
24
0
Order By: Relevance
“…The expression of recombinant enzymes in Escherichia coli and purification to apparent homogeneity for human ADH1A, ADH1B1, ADH1B2, ADH1B3, ADH1C1, ADH1C2, ADH2, ADH3, ADH4, and for human ALDH1A1, ALDH2, ALDH3A1 were carried out as described previously [6,15,29]. All of the isolated recombinant enzyme forms exhibited a single coomassie blue-staining protein band with molecular masses of 40 kDa, 55 kDa, and 54 kDa for ADHs, ALDH1A1/2, and ALDH3A1, respectively, on SDS-polyacrylamide gel electrophoresis.…”
Section: Expression and Purification Of Human Adh And Aldhmentioning
confidence: 99%
“…The expression of recombinant enzymes in Escherichia coli and purification to apparent homogeneity for human ADH1A, ADH1B1, ADH1B2, ADH1B3, ADH1C1, ADH1C2, ADH2, ADH3, ADH4, and for human ALDH1A1, ALDH2, ALDH3A1 were carried out as described previously [6,15,29]. All of the isolated recombinant enzyme forms exhibited a single coomassie blue-staining protein band with molecular masses of 40 kDa, 55 kDa, and 54 kDa for ADHs, ALDH1A1/2, and ALDH3A1, respectively, on SDS-polyacrylamide gel electrophoresis.…”
Section: Expression and Purification Of Human Adh And Aldhmentioning
confidence: 99%
“…Thus, pancreatic stellate cells are intimately involved in the regulation of both physiologic, as well as pathologic aspects of the pancreas [64,65] . Both rat and human pancreatic stellate cells express ADH [66,67] . Furthermore, ADH activity is up regulated in pancreatic stellate cells of individuals suffering from chronic pancreatitis and pancreatic cancer [67] .…”
Section: Involvement Of Pancreatic Stellate Cells In Alcoholic Pancrementioning
confidence: 99%
“…Both rat and human pancreatic stellate cells express ADH [66,67] . Furthermore, ADH activity is up regulated in pancreatic stellate cells of individuals suffering from chronic pancreatitis and pancreatic cancer [67] . The fact that pancreatic stellate cells express ADH indicates that these cells can produce acetaldehyde when exposed to ethanol.…”
Section: Involvement Of Pancreatic Stellate Cells In Alcoholic Pancrementioning
confidence: 99%
“…The ALDH activity in the pancreas is nearly fivefold lower than that of the liver, contributing in this way to acetaldehyde glandular accumulation [110]. Despite this fact, data from animal studies have shown that acetaldehyde by itself does not elicit directly acute pancreatitis [111,112].…”
Section: Harmful Effects Of Acetaldehyde and Fatty Acid Ethyl Esters mentioning
confidence: 95%